Assessment of Knowledge, Attitudes and Practice on Prevention of Sparganosis Infection among Inhabitants of Babati District, Tanzania - J. Kavana Nicholas (Journal of Veterinary Healthcare, 2017)
The knowledge,attitudes, and practice among inhabitants of Babati district in Tanzania on sparganosis were evaluated. A cross-sectional study was carried out among 160 participants from the district. Demographic and socioeconomic information of the participants and their KAP on sparganosis was collected by using a pre-tested questionnaire. All 160(100%) participants had no knowledge about sparganosis. Regarding attitude of participants to keeping dogs and cats; all 160 (100%) participants were not aware of dangers associated with dogs and cats to transmission of sparganosis. 39 (30.0%) of the participants had knowledge of drinking boiled water. There is a need to organise health education programme about sparganosis to increase community knowledge.
Keywords: Knowledge